Strategi Multidimensional dalam Penanganan dan Pencegahan Stunting melalui Program Kesehatan, Lingkungan, dan Hukum di Kelurahan Kaligangsa - Susilowati, Nurdian; Saputri, Atha Difa; Devana Nazwa, Syarla; Najkhan, Azka (Jurnal Bina Desa, 2025)
This study aims to address and prevent stunting in Kaligangsa Village through a multidimensional approach. The methods used include data collection, home visits, education, and provision of nutritious food. Initial data showed that there were 38 children with stunting out of a total of 191 toddlers. Educational activities include the importance of environmental cleanliness, provision of nutritious food, and health rights for women. The "Healthy Kitchen Overcomes Stunting" program which was implemented with cooking demonstrations and direct food provision aims to improve community knowledge and children's nutritional status. The "Brother-Sister Foster" program was implemented to monitor child development by providing education about nutrition, healthy parenting patterns, and health measurement techniques, including evaluation of height, weight, arm circumference, and head circumference. The results showed an increase in community knowledge about nutrition and an improvement in the nutritional status of toddlers. The implications of this activity are a decrease in stunting rates and an increase in child welfare through a holistic and sustainable approach and improving child welfare in the area through a holistic and integrated approach.